Egg grading - Daniel, Bryan; Maddox, Bill. (Lubbock, Tex. : Creative Educational Video, 1987)
Dr. W.F. Krueger, Professor at Texas A & M University, discusses knowledge and skills of poultry science judging contests.
Fakulti Perubatan Veterinar
Keywords: Eggs -- Grading